Novel performance assessment indices for domestic water use - Vieira, P. (2015)
This paper presents a novel methodology for evaluating the efficiency of indoor domestic water use based on performance assessment functions that convert state variables (e.g. flow rate, volume) into performance indices ranging from 0 (the lowest performance) to 300 (excellent performance). Performance functions have been developed for the most common water use devices in the household. An overall household water use index was obtained from the individual water use device indices by weighting each device in accordance with the consumption structure of the household. The application of this methodology to 43 households allowed the quantification of potential water savings and the identification of device-specific measures to increase the water use efficiency